A study of prevalence and factors associated with language delay among 0-3 year old children in a tertiary teaching hospital - Raju, Arunkumar; S., Bharanidharan (International Journal of Contemporary Pediatrics, 2020)
Background: Speech and language are essential components of child development. Delay in language development leads to poor scholastic performance, learning disabilities and poor socialization. Language Evaluation Scale Trivandrum (LEST) is a screening tool for use in office and communities for identifying language delay. Methods: A descriptive study of cross-sectional design was done in 350 children between 0 and 36 months attending well baby clinic. A proforma with demographic details of parents, antenatal, perinatal risk factors were completed. All mothers were asked to complete home screening questionnaire to assess home environment. Language delay was identified using LEST scale. The association of language delay with antenatal, perinatal risk factors, socio economic status and home environment were analyzed. Results: The prevalence of language delay was 6%. No association was found between language delay and type of family, place of residence, antenatal complications, perinatal complications, gestational age, birth weight and socio-economic status. Negative home environment was significantly associated with language delay. Conclusions: The prevalence of language delay was 6%. Negative home environment significantly affects speech and language development